2005
DOI: 10.1055/s-2005-866799
|View full text |Cite
|
Sign up to set email alerts
|

Integriertes Skills-Lab-Konzept für die studentische Ausbildung in der Inneren Medizin

Abstract: This pilot study shows that curriculum changes promoting basic clinical skills are effective and lead to an improved practical education of tomorrow's physicians. The integrated skills laboratory concept is well accepted and leads to a relevant increase in competence in the practice of internal medical. The presented skills laboratory concept in internal medicine is proving to be a viable and efficient learning tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 6 publications
(8 reference statements)
0
19
0
6
Order By: Relevance
“…and the overheads (staff, consumables etc.) are very costly [11], [18]. Currently the TiHo skills lab has more than 40 models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and the overheads (staff, consumables etc.) are very costly [11], [18]. Currently the TiHo skills lab has more than 40 models.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have confirmed their effectiveness in conveying practical skills in tandem with the possibility of checking the competences acquired [14], [15], [16], [17]. As well as the variety of training opportunities on offer, it has also been shown that the concept of training students in skills labs contributes to an improvement in procedural competences [18]. As well as delivering the required theoretical knowledge, the acquisition of practical skills requires intensive practice with the possibility of repetition.…”
Section: Descriptionmentioning
confidence: 99%
“…Herausforderungen bei der Umsetzung sind der relativ hohe personelle und räumli-che Aufwand aufgrund der Kleingruppenarbeit und der notwendigen Tutorenschulungen [30]. [24]. Herausforderungen bei der Umsetzung sind die Anschaffung der z. T. teuren Modelle und ausreichende Personalkapazitä-ten, um den Unterricht in Kleingruppen und unter entsprechender fachkundiger Supervision durchführen zu können.…”
Section: Problemorientiertes Lernenunclassified
“…Einzelne praktische Fertigkeiten können gut mithilfe einer "objective standard clinical evaluation" (OSCE) geprüft werden. Diese Prü-fungsform findet zunehmend Verbreitung an deutschen Universitäten [5,20,34,43]. Für die Prüfung von Diagnostik und Therapie komplexer klinischer Zusammenhän-ge eignen sich simulationsbasierte Szenarien [38], die als Prüfungsmethode gut von Studierenden und Prüfern angenommen werden [30].…”
Section: Simulation Als Prüfungswerkzeugunclassified